2019
DOI: 10.1007/s12182-019-00368-2
|View full text |Cite
|
Sign up to set email alerts
|

3D variable-grid full-waveform inversion on GPU

Abstract: Full-waveform inversion (FWI) is a powerful tool to reconstruct subsurface geophysical parameters with high resolution. As 3D surveys become widely implemented, corresponding 3D processing techniques are required to solve complex geological cases, while a large amount of computation is the most challenging problem. We propose an adaptive variable-grid 3D FWI on graphics processing unit devices to improve computational efficiency without losing accuracy. The irregular-grid discretization strategy is based on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 37 publications
(42 reference statements)
0
9
0
Order By: Relevance
“…Mitigating this problem, except the advance of computer hardware, optimization on inversion algorithms, numerical wavefield modeling and computer codes are important research directions. Among them, (Yao et al 2019c) improving the inversion and modeling algorithms are the key directions because computer code optimization, for example, load balance between processes, CPU vectorization, cache reuse and GPU acceleration (e.g., Wang et al 2019), can only speed up the inversion in tens of times or less generally. Insufficient information restricted by the technology and space of acquisition, the acquired seismic data are incomplete in spatial coverage and frequencies.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…Mitigating this problem, except the advance of computer hardware, optimization on inversion algorithms, numerical wavefield modeling and computer codes are important research directions. Among them, (Yao et al 2019c) improving the inversion and modeling algorithms are the key directions because computer code optimization, for example, load balance between processes, CPU vectorization, cache reuse and GPU acceleration (e.g., Wang et al 2019), can only speed up the inversion in tens of times or less generally. Insufficient information restricted by the technology and space of acquisition, the acquired seismic data are incomplete in spatial coverage and frequencies.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…We found that it is not necessary to include all 25 channels in the input due to the redundancy among seismic data records, so our input only contains 8 channels (6,7,8,11,13,16,17,18). See Figure 11 for an explanation of these serial numbers.…”
Section: ) Training Configurationsmentioning
confidence: 99%
“…As 3D surveys become widely implemented, 3D FWI are required to solve complex geological cases [4], [5], [6]. However, both the computational cost of forward-modeling and the gradient calculation are much higher in the 3D cases than the 2D cases [7], [8]. Thus 3D FWI is still a challenging problem due to the high computational cost.…”
Section: Introductionmentioning
confidence: 99%
“…In geophysics, previous studies have attempted to overcome these computational limitations through different approaches. Some of these studies have focused on the fact that, in FWI, most of the computational time is spent modelling wave propagation 5,6 , which requires the full numerical solution of the acoustic wave equation over discrete grids. The size of the grid is controlled by the acoustic properties of the imaging target and the temporal frequencies involved.…”
Section: Introductionmentioning
confidence: 99%
“…Because the grid spacing could be larger during the inversion of low frequencies, using a fixed grid results in oversampling and redundant computations. For this reason, previous studies have explored the use of adaptive grids, where the grid spacing changes with the background acoustic velocity 5,7 or the frequency of the propagated wave 8 , thus allowing the use of a lower number of grid points with respect to conventional FWI.…”
Section: Introductionmentioning
confidence: 99%